What about Wut ? : a conversation analysis (CA) approach to the Singapore Colloquial English (SCE) particle Wut. - Sountharavalli Mudhlie. (2013)
This study is concerned with the conversation analysis (CA) perspective of the Singapore Colloquial English (SCE) particle wut. Utterances containing wut in two naturally-occurring conversations were extracted, classified and analyzed according to the actions the utterances were performing. Based on the examples gathered, participants had permitted the particle wut in utterances that performed the actions of objecting, reminding, inviting and agreeing. The permissibility and compatibility of wut across all these varied actions all point to wut’s ability to function as an information checking device in conversations. These findings not only inform us how significant a linguistic resource the particle wut is, but also raises important implications for previous studies on wut. Furthermore, this study signals the need for more holistic studies of SCE particles that are grounded in naturalistic data.